The Impact of MJO-C and MJO-B Upon Sea Surface Temperature and Rainfall in Indonesia - Wana Paksi, Lalu Mantigi; Tubalawony, Simon; Waas, Harold Joppie Davido; Muthmainnah, Karisma R. (Journal Omni-Akuatika, 2023)
Madden Julian Oscillation (MJO) based on its propagation through the maritime continent can be divided into two types, namely MJO-C (Crossing) and MJO-B (Blocked) as evidenced by the spatial diagram of Hovmöller OLR anomaly. This study aimed to determine the effect of MJO variations, namely MJO-C and MJO-B on sea surface temperature and rainfall in the Indonesian region in the period of 1998 to 2015. The data used in this study are reanalysis models including sea surface temperature and rainfall with composite events (one month before propagation, during propagation, and one month after propagation of MJO-C and MJO-B). The results show that when MJO-C and MJO-B are active, sea surface temperature and the amount of rainfall are increased, especially in equatorial Indonesia and the southern hemisphere. When compared, MJO-C has a more significant impact than MJO-B.Keywords: MJO, Sea Surface Temperature, Precipitation